'Treat them into the grave': cancer physicians' attitudes towards the use of high‐cost cancer medicines at the end of life. Issue 2 (20th November 2018) - Wiersma, Miriam; Ghinea, Narcyz; Kerridge, Ian; Lipworth, Wendy
Abstract: The prescribing of high‐cost cancer medicines at the end of life has become a focus of criticism, due primarily to concerns about the safety, efficacy and cost‐effectiveness of these medicines in this clinical context. In response to these concerns, a number of interventions have been proposed – frequently focused on improving physician–patient communication at the end of life. Underpinning these strategies is the assumption that the prescribing of high‐cost cancer medicines at the end of life is primarily the result of poor communication on the part of cancer physicians. In this paper, we explore the factors perceived by cancer physicians to be driving the use of high‐cost cancer medicines at the end of life. Drawing on semi‐structured interviews with 16 Australian oncologists and haematologists, we demonstrate that these physicians believe that the use of high‐cost medicines at the end of life is driven by multiple factors – including individual, interpersonal, socio‐cultural and public policy influences. We conclude that these factors, and their interactions, need to be taken into account in the development of public policy and clinical interventions to address the use of high‐cost medicines at the end of life.